Urban Greylag Geese Anser anser nesting on roofs in the city of Hamburg, northern Germany - Hinrichs, Simon; Berthoud, Jean-Louis; Woog, Friederike (Wildfowl, 2025)
Greylag Geese Anser anser usually nest on the ground, close to water. In Hamburg, northern Germany, a pair of urban Greylag Geese was first seen nesting on a roof terrace of a building, 25 m above ground level, in 2013. Since then, the number of breeding pairs showing this unusual behaviour has steadily increased to 21 pairs nesting on roofs in the city in 2024. Hatchlings appeared unable to leave leave these new nesting locations on their own and required human intervention to reach ground level. This type of nesting behaviour now seems to have become established in Hamburg’s Greylag Geese. As far as we know, there have been no previous reports of this behaviour in other towns or cities, and it therefore represents a new aspect in the species’ urban ecology.